Pengaruh Literasi Keuangan, Teknologi Digital, Dukungan Keluarga, dan Sosial Media terhadap Perilaku Konsumtif Mahasiswa - Eka Lutfi Fitria; Kadeni Kadeni (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the influence of financial literacy, digital technology use, family support, and social media on consumer behavior of Bhinneka PGRI Tulungagung University students in the context of the digital economy. Using a quantitative approach, data were collected through questionnaires distributed to 86 student respondents. The data analysis process involved a series of stages such as instrument validity and reliability testing, multiple linear regression analysis, classical assumption testing, t-test, f-test, and coefficient of determination (R²) analysis. The results showed that partially, three independent variables—digital technology use, family support, and social media—have a positive and significant influence on student purchasing decisions. Meanwhile, financial literacy did not show a statistically significant influence. However, when tested simultaneously, the four variables together have a significant influence on student consumer behavior in making purchasing decisions. Of these four factors, digital technology use is the most dominant variable in influencing student consumer behavior. This indicates that students are highly dependent on technology in carrying out consumption activities, from information search to transaction processing. Family support and the influence of social media also contribute to shaping preferences and purchasing decisions. Overall, student consumer behavior in the digital age is heavily influenced by social and technological factors. These findings highlight the importance of improving financial literacy among students, as well as the need for wise use of technology and social media to prevent excessive and uncontrolled consumer behavior.